Acute effects of three different stretching techniques on hamstring flexibility in professional football players - Erkan Erol; Ramazan Yildiz; Ayse Yildiz; Fatih Emre Dogan; Bulent Elbasan (Baltic Journal of Health and Physical Activity, 2023)
Introduction: Hamstring injuries are common in physically active people and athletes. Lack of hamstring flexibility is the one of the most important characteristics of hamstring injuries in athletes. The aim of this study was to investigate effects of three different stretching techniques on hamstring flexibility in professional football players. Materials and Methods: Fifty-five male football players between the ages of 18–20 years old were involved in the study. The participants were divided into 3 groups: static stretching, neuromobilization and Mulligan traction straight leg raise (TSLR), respectively. Each participant’s dominant lower extremity was assessed with a straight leg raise test (SLR) using a goniometer before and after the intervention. Results: There was a significant difference in the SLR range of motion before and after the intervention in all groups. There was no difference in the range of SLR between the groups at the beginning and at the end. However, the increase in the SLR range of motion was significantly higher in the Mulligan TSLR group. Conclusions: It was concluded that all 3 stretching techniques are effective in increasing hamstring flexibility in football players. However, the Mulligan TSLR technique could provide a greater increase in the range of motion than other techniques.